Chlorfenapyr-related delayed rhabdomyolysis: a case series - Xu, Lina; Zhou, Qian; Li, Yan; Ren, Sisi; Hu, Yubin; Wang, Jieru (Frontiers in Neurology, 2025)
IntroductionChlorfenapyr, a broad-spectrum insecticide and acaricide of the pyrrole-class pesticides, can induce dizziness, fatigue, profuse sweating, and altered consciousness by interfering with cell energy metabolism. However, chlorfenapyr-related rhabdomyolysis has rarely been reported.Case presentationsPatient 1 was a healthy 26-year-old man who ingested approximately 30 mL of chlorfenapyr. After gastric lavage, rehydration, diuresis, liver protection, and symptomatic treatment, he was discharged. However, he was readmitted 11 days later with rhabdomyolysis and acute kidney injury, and his blood tralopyril level was 187 μg/mL. Patient 2 was a 43-year-old man who consumed approximately 50 mL of chlorfenapyr without seeking medical care for 6 days. On day 7, his blood chlorfenapyr and tralopyril levels were 42 μg/mL and 542 μg/mL, respectively. Subsequently, the patient was diagnosed with rhabdomyolysis and brainstem injury.DiscussionChlorfenapyr can disrupt cellular energy metabolism, leading to rhabdomyolysis and brainstem injury, and physical activity may trigger and accelerate rhabdomyolysis. The delayed damage caused by chlorfenapyr poisoning may be attributed to the gradual depletion of cellular energy and prolonged presence of its metabolites in the body.